Gonadotropin-releasing Hormone Stimulation Test for Precocious Puberty - Kim, Han Kyul (The Korean Society for Laboratory Medicine, 2011)
BACKGROUND: Gonadotropin-releasing hormone (GnRH) stimulation test is the gold standard to identify central precocious puberty (CPP). This test requires multiple blood samples at different time points to measure gonadotropin levels, and is therefore expensive, time-consuming, and uncomfortable for patients. We aimed to simplify the GnRH stimulation test to require fewer blood samples. METHODS: A study of 166 girls with precocious puberty was undertaken. Blood samples were obtained at 0, 15, 30, 45, 60, 90, and 120 min after GnRH administration, and the levels of luteinizing hormone (LH) and follicle-stimulating hormone (FSH) were measured. For each parameter, the sensitivities and specificities were estimated and ROC curves were constructed. RESULTS: One hundred and twenty-eight patients (77.1%) were diagnosed for CPP. Peak LH levels were achieved 30 min after GnRH stimulation in patients with CPP. Further, 98.4% of the 45-min samples were diagnostic for CPP, and the cumulative frequency of LH values of ≥5 IU/L was 100% at 45 min. Using this cut-off value for LH, the ROC curve for LH at 45 min showed the highest sensitivity (98.4%) and specificity (100%) in the diagnosis of CPP. CONCLUSIONS: Values of LH measured from a single blood sample obtained at 45 min in the GnRH stimulation test may be adequate for the diagnosis of CPP. Two samples, taken at 30 and 45 min after stimulation, were able to accurately diagnose CPP in 100% of the patients in this study.